The impact of an encounter with a gynaecologic dermatologist on quality of life, health literacy and education satisfaction for patients with vulvar lichen sclerosus: A survey study. Issue 3 (30th December 2021) - Kolitz, E. M.; Pineider, J.; Mauskar, M. M.; Rutherford, A.
Abstract :